PERKEMBANGAN FINANCIAL TECHNOLOGY (FINTECH) LENDING SYARIAH; TINJAUAN TERHADAP KONSEP, PENGAWASAN DAN REGULASI - Heris Suhendar; Ayon Diniyanto (Jurusan Hukum Ekonomi Syariah Fakultas Syariah dan Hukum Uin Alauddin Makassar, 2020)
The development of sharia fintech lending for three years has increased significantly. Starting from 2018 to 2020 there were twelve sharia fintech lending companies. The existence of sharia fintech lending is regulated by POJK Number: 77 / POJK.01 / 2016. This regulation has not yet developed the concept and operation of business activities, guarantees of certainty regarding the fulfillment of sharia principles, and legal protection of the implementation of sharia fintech lending, thus allowing risks that must be borne properly by the organizers and the fintech users themselves. This study is a normative legal research using a statutory approach and a conceptual approach. This study material was obtained from a literature study, then analyzed in a prescriptive analytical manner for examination and discussion. The results of the analysis are interpreted using systematic, grammatical and teleological interpretation methods. The results of the study concluded that: 1) the collaboration of the contract concept in the DSN-MUI Fatwa Number: 117 / DSN-MUI / II / 2018 and the implementation / operation of business activities in POJK Number: 77 / POJK.01 / 2016 is a benchmark for sharia supervision in the implementation sharia fintech lending; 2) the function of supervising and guaranteeing the fulfillment of sharia principles by the Sharia Supervisory Board; and 3) legal protection in the implementation of sharia fintech lending is still weak, because the POJK Number 77 / POJK.01 / 2016 does not regulate business activities and operations, guarantee compliance with sharia principles, and sharia fintech lending dispute resolution.